The contribution of national research on schooling of students with intellectual disabilities (Research, Society and Development, 2018)
Considering the current policies and the movement of school inclusion, it is important to investigate how research is addressing this issue and see what they advance. The objective was to identify what the national researchs says about the forms and types of schooling for students with intellectual disabilities. To this end, it carried out a literature review of theses and dissertations for the period 2010-2016. The analysis of 32 productions allowed the organization in seven thematic categories. The researchs show difficulty to evaluate and rank effective strategies for school inclusion of students with ID. It concludes the need for joint reflection on teaching practices, coensino, shared teaching and collaborative teaching as viable alternatives for the true construction of a teaching and a truly inclusive practice.